Intracellular Magnetic Labeling of Lymphocytes for In Vivo Trafficking Studies. (April 1998) - Schoepf, U.; Marecos, E.M.; Melder, R.J.; Jain, R.K.; Weissleder, R.
Lymphocyte adhesion and trafficking is difficult to observe in vivo over time. We used magnetic resonance imaging (MRI) to identify magnetically labeled lymphocytes in phantom experiments and in tissue. A method of lymphocyte labeling was developed that is based on fluid-phase endocytosis of nanometer-sized biocompatible superparamagnetic particles. The maximum cell uptake in culture was 0.11 ng Fe/cell corresponding to 5 × 10 6 particles/lymphocyte. Cells stably retained the label and were fully viable for at least 3 days. Labeled lymphocytes showed adhesion to human endothelial cells similar to unlabeled cells, indicating no effect of labeling on cell surface expression of adhesion proteins. No particle-mediated cytotoxicity could be observed. The detection threshold of MRI for detecting labeled lymphocytes in the current study was 2.5 × 10 6 cells/30 μL sampling volume. Following intravenous injection of labeled lymphocytes into rats, cells accumulated in spleen, lymph nodes and liver with a similar bio-distribution as unlabeled cells. Lymphocyte accumulation in the spleen resulted in MRI signal intensity changes readily detectable by MRI. These findings suggest that intracellular lymphocyte labeling with superparamagnetic particles is feasible, does not alter the viability or tissue distribution of labeled cells and allows the detection of labeled lymphocytes by MRI.